2012
DOI: 10.1089/jir.2011.0038
|View full text |Cite
|
Sign up to set email alerts
|

Variance in the Acute Inflammatory Response to Prolonged Cycling Is Linked to Exercise Intensity

Abstract: This study investigated the influence of age, body composition, physical fitness, training volume and intensity, and underlying systemic inflammation on exercise-induced inflammation and innate immune function in a heterogeneous group of cyclists. Subjects included 31 male cyclists (mean ± standard deviation, age 38.8 ± 10.6 years, body fat 17.8%± 5.6%, VO(2max) 55.8 ± 8.4 mL kg(-1) min(-1)) who cycled for 1.75 h at 60% watts(max) followed by a 10-km time trial (18.3 ± 0.3 min). Blood samples were collected pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
63
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 23 publications
8
63
2
2
Order By: Relevance
“…The increased production of cytokines may be associated with different cell types from the immune and other systems [35,36,37]. In the current study, we observed an increase in IL-8 and IL-10 levels immediately after the race that is consistent with the literature [9,38].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The increased production of cytokines may be associated with different cell types from the immune and other systems [35,36,37]. In the current study, we observed an increase in IL-8 and IL-10 levels immediately after the race that is consistent with the literature [9,38].…”
Section: Discussionsupporting
confidence: 92%
“…IL-8, a pro-inflammatory cytokine mainly produced by monocytes, endothelial cells [13] and skeletal muscle [35,36], classically acts as a chemokine that attracts primarily neutrophils and angiogenic factors [35,40]. Moreover, Marsland et al [41] showed increased production of IL-8 in situations of perceived stress during chronic stress and Xiong et al [42] demonstrated important influences of IL-8 on neuronal function, as well as on mood state [13].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, regular highintensity exercise can lead to decreased secretion of cytokines, such as interleukin (IL)-6, tumor necrosis factor (TNF)-α, interferon (IFN)-γ, IL-1β, IL-2, IL-8 and IL-10 [10,11]. Insufficient recovery between periods of prolonged exercise appears to exaggerate these effects [12].…”
Section: Introductionmentioning
confidence: 99%
“…Acute modulations in systemic TNF-a remain controversial, and this response is linked to the volume of the exercise performed. 22 In CKD, for Viana et al, 23 30 min of aerobic exercise in pre-dialysis individuals induced significant elevation of IL-6 and IL-10, with little effect in the TNF receptors (sTNF-RI and sTNF-RII) in post exercise. After one hour from the exercise session, IL-6 and IL-10 remained in higher concentrations and an increase in sTNF-RII was found.…”
Section: Discussionmentioning
confidence: 99%